2019
DOI: 10.1016/j.tiv.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Cellular apoptosis of HFF cells by inorganic nanoparticles not susceptible to modulation by Toxoplasma gondii infection in vitro

Abstract: The interaction of nanoparticles with living cells is becoming one of the urgent areas of collaborative research in materials science and biology. Previously, we showed that nanoparticles have promising anti-Toxoplasma gondii properties. Meanwhile, Toxoplasma gondii has been shown to avert apoptosis in host cells whereas nanoparticles have been implicated for apoptotic tendency. Therefore, in the present study, we assessed the in vitro apoptotic properties of inorganic nanoparticles in the absence or presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our present results indicated that T. gondii controls the NOX4-dependent ROS production in ARPE-19 cells to maintain a strong anti-oxidative environment, and then prolongs its parasitism in the cells. However, Adeyemi et al 40 have recently reported that T. gondii do not modify cellular apoptosis by inorganic NPs in human fibroblast foreskin cells. The biggest differences between these two studies are the infection time of T. gondii into the host cells and the viability of parasites.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our present results indicated that T. gondii controls the NOX4-dependent ROS production in ARPE-19 cells to maintain a strong anti-oxidative environment, and then prolongs its parasitism in the cells. However, Adeyemi et al 40 have recently reported that T. gondii do not modify cellular apoptosis by inorganic NPs in human fibroblast foreskin cells. The biggest differences between these two studies are the infection time of T. gondii into the host cells and the viability of parasites.…”
Section: Discussionmentioning
confidence: 98%
“…[17][18][19][20][21][22][23]41,42 These facts were supported by many other studies mentioning that the inhibitory activity by T. gondii requires live intracellular parasites and ongoing protein synthesis. [19][20][21][22] However, Adeyemi et al 40 treated T. gondii with various NPs to infect human foreskin fibroblasts and then evaluated apoptosis; thus T. gondii may contact NPs immediately and directly and cause damage to invade the host cells. 33,43 Therefore, it would not establish a favorable environment for resisting apoptosis by T. gondii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation